2020
DOI: 10.1016/j.ijid.2020.01.044
|View full text |Cite
|
Sign up to set email alerts
|

Distinctive EBV infection characteristics in children from a developing country

Abstract: Background: In developing countries, Epstein-Barr virus (EBV) infection is mostly asymptomatic in early childhood. EBV persistence may lead to different malignancies, such as B cell derived lymphomas. In Argentina, most children are seropositive at three years and an increased association between EBV and lymphoma was proved in children under 10 years old by our group. Objective: Our aim was to characterize EBV infection at the site of entry and reactivation of viral infection -the tonsils-in order to better un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 38 publications
3
10
0
Order By: Relevance
“…Similarly, in early childhood, EBV infection is asymptomatic or associated with a middisease, whereas it often manifests as an acute infectious mononucleosis in adults because of an exaggerated immune response (27,28). The mechanism underlying the lack of EBV symptoms in early life is not well defined; however, a lower number of new infectious virions is reported to be associated with mild and subclinical symptoms (29). Mechanistically, limited viral Ags because of fewer infectious particles results in immune surveillance avoidance and is subsequently associated with EBV persistence (29).…”
Section: Disease Tolerance To Viral Infections In Infants and Childrenmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, in early childhood, EBV infection is asymptomatic or associated with a middisease, whereas it often manifests as an acute infectious mononucleosis in adults because of an exaggerated immune response (27,28). The mechanism underlying the lack of EBV symptoms in early life is not well defined; however, a lower number of new infectious virions is reported to be associated with mild and subclinical symptoms (29). Mechanistically, limited viral Ags because of fewer infectious particles results in immune surveillance avoidance and is subsequently associated with EBV persistence (29).…”
Section: Disease Tolerance To Viral Infections In Infants and Childrenmentioning
confidence: 99%
“…The mechanism underlying the lack of EBV symptoms in early life is not well defined; however, a lower number of new infectious virions is reported to be associated with mild and subclinical symptoms (29). Mechanistically, limited viral Ags because of fewer infectious particles results in immune surveillance avoidance and is subsequently associated with EBV persistence (29). As such, the occurrence of asymptomatic EBV in early childhood elicits limited virusspecific CD8 + T cells, whereas excessive expansion of CD8 + T cells is the cause of symptoms in adolescents (e.g., acute infectious mononucleosis) (30).…”
Section: Disease Tolerance To Viral Infections In Infants and Childrenmentioning
confidence: 99%
“…For instance, bacterial infectioninduced tonsillitis is primarily treated via antibiotics clinically [19,20], although, EBV induced tonsillitis should be given antiviral therapy [21]. Recent findings have shown that EBV is asymptomatic in many children and varies in pathogenicity depending on the degree of virus infection [22].…”
Section: Discussionmentioning
confidence: 99%
“…For the surgery to be performed, patients must be completely asymptomatic, without signs or symptoms of acute inflammation or infection such as fever, sore throat, or cough. At surgery, a concomitant blood sample was obtained and serum was separated to determine the EBV infection status using indirect immunofluorescence assay, as previously reported ( 16 ). A portion of the tissue was preserved at −70°C for later nucleic acid extraction, and the remaining biopsy tissue was formalin-fixed paraffin-embedded (FFPE) at the Pathology Division of Ricardo Gutierrez Children’s Hospital (Buenos Aires, Argentina).…”
Section: Methodsmentioning
confidence: 99%